Small businesses in the aftermath of the crisis : International analyses and policies - Favaretto, Ilario; Calcagnini, Giorgio (Contributions to Economics, 2012)
This book seeks to analyze how small and medium businesses react to the economic and financial crisis. Its focus is on the activities and strategies of SMEs in the areas of innovation, R&D investment, labor markets and finance. The book takes an international perspective and includes both comparative and national analyses and policies, with authors representing acdemia and international institutions such as the ECB, OECD, Kauffman Foundation, Federal Reserve, and US Small Business Administration.